Membangun Norma Guru dalam Organisasi Sekolah Islam - Rahmat Pauzi, Ega (Al-Qiyadi Jurnal Manajmen Pendidikan Islam, 2024)
This paper aims to understand the norms built among educators in the network of Islamic school organizations. This research uses qualitative research methods. In addition to relying on literature studies and interviews, the author was directly involved in activities organized by the Garut Integrated Islamic School Network (JSIT). The results showed that the norms that live in this network of Integrated Islamic Schools cannot be separated from the influence of the tarbiyah movement as the background of the members' da'wah activities. In addition to the Islamic character of the founders, this norm has also become a mission that must exist in every Integrated Islamic School. However, not all schools labeled as Integrated Islamic Schools capture this mission. The Garut Integrated Islamic School Network ensures this norm can live among its member schools.